Anatomy, chlorophyll content and photosynthetic performance in currentyear and previous-year Aleppo pine (Pinus halepensis Mill.) needles - Tomo Trstenjak; Jasenka Antunović Dunić; Selma Mlinarić; Lidija Begović; Marin Škoro; Vera Cesar; Hrvoje Lepeduš (Botanica Serbica, 2020)
Aleppo pine (Pinus halepensis) is a widespread Mediterranean woody species. Needles usually fall off the tree after the second year, which can be the reason for substantial crown defoliation under extreme environmental stress. The aim of the present investigation was to compare the anatomy, chlorophyll content and photosynthetic performance in current-year (CY) and previous-year (PY) Aleppo pine needles. Chlorophyll concentrations were determined spectrophotometrically, while photosynthetic performance was determined by measuring the increase in chlorophyll a fluorescence (the JIP test). The obtained results revealed that concentrations of chlorophylls a and b were almost twice as great in PY needles as in CY ones. The chlorophyll a to b ratio and values of the maximum quantum yield of photosystem II (Fv/Fm) showed no statistically significant difference between CY and PY needles. However, the performance index (PIABS) was significantly higher in CY needles compared to PY ones. Analysis of PIABS components revealed that CY needles had increased electron transport beyond the primary electron acceptor, QA -, which was associated with a lower value of variable fluorescence at 2 ms (VJ ) in comparison with PY needles. Also, some differences were observed in needle anatomy. Current-year needles had an increased proportion of mesophyll tissue, together with decreased proportions of vascular cylinder and resin duct areas. Also, many more starch grains were present in PY than in CY needles. Based on the presented results, it can be concluded that despite considerably lower chlorophyll content, CY needles exhibited photosynthetic performance better than that of older needles, which is an unusual phenomenon in woody species